SMEs issues in Lenggong : a case study of the Lenggong Valley World Archeological Heritage Site Malaysia / Mastura Jaafar ... [et al.] - Jaafar, Mastura; Dahalan, Norziani; Mhd Rashid, Munira; Mohd Rosdi, Siti Asma' (2012)
SMEs are fundamental for the economic development of a country. Tourism development has been beneficial in terms of its contribution to the income generation, economic growth, poverty reduction, and improving rural livelihoods. Lenggong Valley which is located in Hulu Perak is one of Malaysia's most significant areas after it has been nominated to U-ESCO as a world heritage site. Lenggong Valley is not only rich with its human civilization, but it also has a variety of products to offer. In relation to tourism development, the contribution of small local community entrepreneurship is significant in producing various agro products such as "serunding", "dodol", "ikan pekasam" and also in running the activities of cattle, goats and deerfarming. Hulu Perak District Local Plan 2002-2015 has come out with the initiative to develop a concept of 'one product one village'. Thus this study reports the achievement of SMEs based on studies done for village within the area of Mukim Durian Pipit & Mukim Temelong.